Light‐Powered Healing of a Wearable Electrical Conductor. (15th September 2014) - Kang, Hong Suk; Kim, Hee‐Tak; Park, Jung‐Ki; Lee, Seungwoo
<x xml:space="preserve">Abstract</x> Mechanical failure along a conductive pathway can cause unexpected shutdown of an electronic devices, ultimately limiting the device lifetime. To address this problem, various systems to realize healable electrical conductors have been proposed; however, rapid, noninvasive, and on‐demand healing, factors that are all synergistically required, especially for wearable device applications, still remains challenging. Here, a light‐powered healable electrical conductor (conceptualized as photofluidic diffusional system) is proposed for simple‐, fast‐, and easy‐to‐implement wearable devices (e.g., the electronic skin, sensitive to mechanical motion). Contrary to other implementations such as capsules, heat, water, and mechanical forces, green light even with low intensity has potential to provide fast (less than 3 min) and repetitive recovery of a damaged electrical conductor without any direct invasion. Also, the multiple, irregular cracks resulting from vigorous motions of wearable devices can be simultaneously recovered regardless of the light incident angles and crack propagation directions, thus, making light‐powered healing more accessible to wearable devices beyond existing system options. To develop and demonstrate the key concepts of this system, combined studies on materials, integrations, and light‐powering strategy for recovering a damaged wearable electrical conductor are systematically carried out in the present work.